Isolation of Phosphate solubilizing bacteria from sorghum bicolor rhizosphere soil inoculated with arbuscular mycorrhizae fungi (Glomus sp) - Chandrasekeran, Angaleswari; P.U., Mahalingam (Research in Biotechnology, 2014)
The presence of phosphorus in parent material is abundant but the soil phosphors availability is limited for plant. Some soil micro-organisms enhance solubility of phosphate in soils. This study investigated the coexistence of phosphate solubilizing microorganism in the rhizosphere soil inoculated with mycorrhizal fungi (AMF) Glomus sp in sorghum bicolor. The rhizosphere soil samples was collected and processed for the presence of phosphate solubilizing microorganisms. The microbes isolated were screened for their efficiency to solubilize the phosphate present in pikovskaya’s medium. Based on the solubilization index five bacterial isolates were chosen for the study. The maximum solubilization index was 1.75 cm by both bacterial isolates 2 and 5 on 6th day of incubation further total inorganic phosphorus produced by the bacterial isolates were determined and it was found to be 1.578 g/L by isolate 5 and 186 mg/L by isolate 2 respectively. The bacterial isolates having the maximum solubilization index and inorganic phosphorus production was identified by the morphological and biochemical tests and found to be Bacillus sp and Micrococcus sp.